PENDEKATAN PEMBELAJARAN STUDENT CENTER (DISCOVERY, INQUIRY, PROBLEM SOLVING LEARNING) DAN IMPLEMENTASINYA DI PONDOK PESANTREN - Muntolib, Muntolib; Tamam, Abas Mansur; Rahman, Imas Kania; Alim, Akmad; Indra, Hasbi (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
National education has a noble goal. To achieve this noble goal is determined by the learning process. The implementation of learning in schools uses more conventional methods that place the teacher as the center of learning resources so that teachers are more involved in the learning process. In this regard, the teacher is in a position to develop a learning model that is able to increase student competence and activeness in learning. Among the learning approaches that can increase competition and student activity is the Student Centered Learning (SCL) learning approach. The purpose of this research is to collect data and information, as well as to study how the Student Centered Learning (SCL) learning model is considered relevant and most effective and how Islam sees this Student Centered Learning (SCL) approach and how it is implemented in Islamic boarding schools. The method used in this research is descriptive qualitative. The results of this study indicate that the Student Center Learning approach is a teaching and learning method that is centered on the needs and interests of students. This learning approach has several models including Discovery Learning, Inquiry Learning, Problem Solving Learning. The methods and characteristics of the Student Center are in line with Islam. As a result, this learning strategy can be utilized in the design of the Student Active Center-based Islamic boarding school curriculum development to encourage students to become active learners.